Analysis of Regional and Income Disparities in Nganjuk Regency: A Study Based on the Williamson Index and Gini Index - Berliyan, Berliyan; Aldy Purnomo, Rochmat; Cahyono, Yeni; Santoso, Slamet; Abas, Sayid (Eduvest - Journal of Universal Studies, 2025)
This study addresses the issue of identifying regional disparity analysis, specifically to provide an overview of the level of development disparity in Nganjuk Regency in relation to welfare levels. By examining the income disparity of the population across regions, we can gain insights into the performance success of the economic development in Nganjuk Regency. This can serve as a foundation for future regional economic development planning. The research method employs descriptive analysis using secondary data from the Central Bureau of Statistics (BPS) of Nganjuk Regency, East Java Province, and Indonesia. The calculations of inter-regional income inequality through the Williamson Index and inter-household income inequality through the Gini Index both conclude that there is a rising trend of income inequality in Nganjuk Regency from 2022 to 2023. This increase in income inequality may be attributed to the economic slowdown in 2023, which impacts both regions and income groups, thus exacerbating disparities between regions and among individuals/households.